2020
DOI: 10.1371/journal.pone.0239865
|View full text |Cite
|
Sign up to set email alerts
|

Split-based points from the Swabian Jura highlight Aurignacian regional signatures

Abstract: The systematic use of antlers and other osseous materials by modern humans marks a set of cultural and technological innovations in the early Upper Paleolithic, as is seen most clearly in the Aurignacian. Split-based points, which are one of the most common osseous tools, are present throughout most regions where the Aurignacian is documented. Using results from recent and ongoing excavations at Geißenklösterle, Hohle Fels and Vogelherd, we nearly tripled the sample of split-based points from 31 to 87 specimen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 57 publications
0
9
0
Order By: Relevance
“…Whenever the base of the projectile points is preserved, it is a simple/massive point, of the variety defined as 'elongated objects with a pointed distal tip, a variable cross-section (mostly elliptical) and a simple hafting system' [67:1, 68]. Though such items are frequently fabricated on antler, especially in the earlies phases of the UP both in Europe and the Levant [69][70][71][72][73][74][75][76][77], in Dzudzuana they are mostly of bone. Indeed, antler working is quite rare at the site.…”
Section: Plos Onementioning
confidence: 99%
“…Whenever the base of the projectile points is preserved, it is a simple/massive point, of the variety defined as 'elongated objects with a pointed distal tip, a variable cross-section (mostly elliptical) and a simple hafting system' [67:1, 68]. Though such items are frequently fabricated on antler, especially in the earlies phases of the UP both in Europe and the Levant [69][70][71][72][73][74][75][76][77], in Dzudzuana they are mostly of bone. Indeed, antler working is quite rare at the site.…”
Section: Plos Onementioning
confidence: 99%
“…Conversely, no bone tools are yet described from layers rsa' and ars 76 . Split-based antler points 114,115 have not been recovered at Castelcivita. Available data suggests that the split-based points www.nature.com/scientificreports/ recovered across Italy are generally dated after the CI super-eruption 116 , indicating that this tool type spread south of the Alps in a subsequent phase of the EA 27 .…”
Section: Exploring Alternative Scenarios and Mapping Future Research ...mentioning
confidence: 99%
“…The Neanderthal fossil from Hohlenstein-Stadel is one of the few known remains of Paleolithic hominins from the Swabian Jura. The paleoanthropological analysis identified a femur shaft with robust features and taphonomic observation revealed that it was gnawed on by a mid-to large-sized carnivore, a hyena being the most likely candidate (Camarós et al 2016;Kitagawa 2014;Kunter and Wahl 1992). Mitochondrial DNA analysis demonstrates that this lineage diverged ~270 ka from other Neanderthals and that the diversity of their population was greater compared to the populations that existed later in the MP (Posth et al 2017).…”
Section: Neanderthal Fossilmentioning
confidence: 99%